Reflections on the irpado or animal wedding in Highland Andeanherding rituals - Elizaga Coulombié, Julieta (2024)
In this study, we explore the concept of irpado within the context of the señalakuy ritual. Described by shepherds as an «animal marriage», it refers to the selection of two animals, breeding in the upcoming year. The term encompasses two main meanings: the actions of guiding and accompanying, possibly related to interregional travels and herding, and the symbolic connection between birds and camelids, as indicated by its translation to pichón. This prompts an investigation into the dynamics between High Andean shepherds and their flocks.